Foreign direct investment, investment agreements and economic development: Myths and realities - Yılmaz Akyüz (South Centre, 2015)
Foreign direct investment (FDI) is one of the most ambiguous and the least understood concepts in international economics. Common debate on FDI is confounded by several myths regarding its nature and impact on capital accumulation, technological progress, industrialization and growth. It is often portrayed as a long term, stable, cross-border flow of capital that adds to productive capacity, helps meet balance-of-payments shortfalls, transfers technology and management skills, and links domestic firms with wider global markets. However, none of these are intrinsic qualities of FDI.
Keywords: 300; Auslandsinvestition; Handelsabkommen; Zahlungsbilanz; Investitionspolitik; Wirtschaftswachstum; Entwicklungsländer; Welt